A proposed sustainable and digital collection and classification center model to manage e-waste in emerging economies. Issue 1 (19th June 2020) - Kazancoglu, Yigit; Ozbiltekin, Melisa; Ozkan Ozen, Yesim Deniz; Sagnak, Muhittin
Abstract : Purpose: This study aims to propose an electronic waste collection and classification system to enhance social, environmental and economic sustainability by integrating data-driven technologies in emerging economies. Design/methodology/approach: GM (1, 1) model under grey prediction is used in this study in order to estimate the trend of the amount of collected electronic waste in emerging economies. Findings: It is revealed that the amount of collected electronic waste is increasing day by day, and within the framework of sustainability in the process of collecting and classification of electronic waste, digital technologies were found to be lacking. It has been determined that this deficiency, together with the increasing amount of electronic waste, has caused environmental, social and economic damage to emerging economies. Originality/value: The main originality of this study is integrating electronic waste collection and classification processes with data-driven technologies and sustainability, which is a relatively new subject.